MODEL PARIWISATA BERBASIS TRI HITA KARANA: STUDI KASUS PENGELOLAAN KAWASAN LUAR PURA ULUWATU - Ida Bagus Gde Pujaastawa; I Putu Sudana (Universitas Andalas, 2022)
This study tries to examine the management model of Kawasan Luar Pura Uluwatu Tourist attraction in Pecatu Village, Bali, one of the popular tourist attractions and is considered to have implications that lead to increasing economic welfare, cultural and environmental sustainability. The purpose of this research is to formulate a tourism attraction management model based on Tri Hita Karana as an alternative model for sustainable tourism development. This research was conducted using an ethnographic approach as a variant of the qualitative approach. Data was collected by using interviews, observation, literature, and document inspection techniques. The findings of this study state that the Tri Hita Karana-based tourist attraction management model makes the three environmental aspects (spiritual, social, and physical) objects as well as subjects of tourism development. In their position as objects, aspects of parhyangan, pawongan, and palemahan function as potential tourist attractions. On the other hand, as a subject, the values of Tri Hita Karana serve as a reference as well as control tourism development policies. This model carries a number of implications in the form of increasing economic welfare, and cultural and environmental sustainability in a sustainable manner.